The Effect of Farm Credits on Crop Production In Jambalul, Afgoia –Somalia - Abdulkadir, Mohamed Osman; Hassan, Mohamed Mohamud; Ahmed, Abdirahman Mohamed; Omar, Shire Hassan (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
Farm credit plays a pivotal role in agrarian and rural development as it allows farmersgain economies of scale, venture into new fields of production, engage new technologies andenable them to provide utilities for a broadening market so this paper aims to examine the effectsof farm credits on crop production in Jambalul, Afgoia and to find out the magnitude of the farmcredit services with the findings in Jambalul, Afgoia, and Lower Shebelle in Somalia.A survey research method has been adopted to examine the effects of farm credits on cropproduction in Jambalul, Afgoia. The data were collected through questionnaires filled by therespondents and the survey respondents were asked to rate eighteen questions developed from thethree objectives of the study.The results indicated that farm credits is an important tool for the production of crops throughproviding of loans and setting stable rural economic community. Farm credits improve the livingstandard of farmers by increasing their yielding and reducing the poverty.